Histone Deacetylase 1 Plays an Acetylation-Independent Role in Influenza A Virus Replication - Chen, Lin; Wang, Chengmin; Luo, Jing; Su, Wen; Li, Meng; Zhao, Na; Lyu, Wenting; Attaran, Hamidreza; He, Yapeng; Ding, Hua; He, Hongxuan (Frontiers in Immunology, 2017)
Influenza A viruses (IAVs) take advantage of the host acetylation system for their own benefit. Whether the nucleoprotein (NP) of IAVs undergoes acetylation and the interaction between the NP and the class I histone deacetylases (HDACs) were largely unknown. Here, we showed that the NP protein of IAV interacted with HDAC1, which downregulated the acetylation level of NP. Using mass spectrometry, we identified lysine 103 as an acetylation site of the NP. Compared with wild-type protein, two K103 NP mutants, K103A and K103R, enhanced replication efficiency of the recombinant viruses in vitro. We further demonstrated that HDAC1 facilitated viral replication via two paths: promoting the nuclear retention of NP and inhibiting TBK1-IRF3 pathway. Our results lead to a new mechanism for regulating NP acetylation, indicating that HDAC1 may be a possible target for antiviral drugs.